Membrane filtration of alkali-depolymerised kraft lignin for biological conversion. (September 2019) - Abdelaziz, Omar Y.; Ravi, Krithika; Nöbel, Matthias; Tunå, Per; Turner, Charlotta; Hulteberg, Christian P.
Abstract: In this study, we have investigated the possibility of membrane filtration as a means for obtaining a fraction containing mainly low-molecular-weight (LMW) compounds from depolymerised lignin (DL) for subsequent microbial conversion. A DL stream from continuous-mode alkali depolymerisation of a softwood kraft lignin produced at a temperature of 220 °C and a residence time of 2 min, using a NaOH/lignin weight ratio of 1 with 5 wt% lignin loading was fractionated using a polymeric membrane with a molecular weight cut-off of 500–700 Da. The permeate (DLP) volume recovery of LMW phenolics (250–450 Da) was 70% after filtration for 3.7 h. The DLP was used as a carbon source for growth of three bacterial strains; Pseudomonas fluorescens, P. putida EM42 and Rhodococcus opacus, and good growth was obtained by the first two microorganisms. This proof-of-concept study demonstrates a novel strategy for technical lignin valorisation by combining depolymerisation, nanofiltration and bioconversion.